The Bacillus subtilis primosomal protein DnaD untwists supercoiled DNA - Zhang, Wenke; Allen, Stephanie; Roberts, Clive J.; Soultanas, Panos (2006)
The essential Bacillus subtilis DnaD and DnaB proteins have been implicated in the initiation of DNA replication. Recently, DNA remodeling activities associated with both proteins were discovered that could provide a link between global or local nucleoid remodeling and initiation of replication. DnaD forms scaffolds and opens up supercoiled plasmids without nicking to form open circular complexes, while DnaB acts as a lateral compaction protein. Here we show that DnaD-mediated opening of supercoiled plasmids is accompanied by significant untwisting of DNA. The net result is the conversion of writhe (Wr) into negative twist (Tw), thus maintaining the linking number (Lk) constant. These changes in supercoiling will reduce the considerable energy required to open up closed circular plectonemic DNA and may be significant in the priming of DNA replication. By comparison, DnaB does not affect significantly the supercoiling of plasmids. Binding of the DnaD C-terminal domain (Cd) to DNA is not sufficient to convert Wr into negative Tw, implying that the formation of scaffolds is essential for duplex untwisting. Overall, our data suggest that the topological effects of the two proteins on supercoiled DNA are different; DnaD opens up, untwists and converts plectonemic DNA to a more paranemic form, whereas DnaB does not affect supercoiling significantly and condenses DNA only via its lateral compaction activity. The significance of these findings in the initiation of DNA replication is discussed.